Prepping the knee in maximal flexion: getting into every nook, cranny, and fold - Peter A. Knoll, MD; James A. Browne, MD (Arthroplasty Today, 2017)
This article describes a simple surgical skin preparation technique for total knee arthroplasty that permits the application of skin prep agent with the knee in maximal flexion. While most surgeons prep the knee in extension, it is believed that prep of the knee in flexion will provide superior coverage of the skin surface and reduce the potential for surgical-site infection, particularly in obese patients with large soft-tissue layers anterior to the knee.